2017
DOI: 10.1111/bjd.15602
|View full text |Cite
|
Sign up to set email alerts
|

Emollients and moisturizers for eczema: abridged Cochrane systematic review includingGRADEassessments

Abstract: Eczema is a chronic inflammatory skin disorder with considerable impact on quality of life. Emollients or moisturizers are widely recommended, but are these effective and safe? We searched for randomized controlled trials (RCTs) in the Cochrane Skin Group Specialised Skin Register, CENTRAL in The Cochrane Library, MEDLINE, Embase, LILACS, the GREAT database and five trial registers to December 2015. We included 77 RCTs with 6603 participants. Seven studies (9%) were at low risk of bias, 34 (44%) had unclear ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 78 publications
0
40
0
5
Order By: Relevance
“…Calcineurin inhibitors are also of limited benefit. Emollients are ineffective, because most patients do not have dry or atopic skin, and are poorly tolerated . Most patients with NE have chronic pruritus and poor quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Calcineurin inhibitors are also of limited benefit. Emollients are ineffective, because most patients do not have dry or atopic skin, and are poorly tolerated . Most patients with NE have chronic pruritus and poor quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, combination therapy with urea was found to be more effective than treatment with hydrocortisone or betamethasone-17-valerate alone (Pan et al, 2013). A recent Cochrane review confirmed that, in AD, treatment with moisturizers and topical corticosteroids is more effective than treatment with topical corticosteroids alone (Van Zuuren, Fedorowicz, & Arents, 2017). A systematic review confirmed the positive effect of moisturizers in AD but alerted to the need for better-designed studies that allow direct comparisons between moisturizing agents (Lindh & Bradley, 2015).…”
Section: Urea and The Functional Integrity Of The Stratum Corneummentioning
confidence: 99%
“…Based on a Cochrane review and vast clinical experience, the application of moisturizers leads to an improvement in AD severity, increases the effect of anti-inflammatory therapies, reduces the number of flares, and decreases the use of TCS [137]. Would it be possible to prevent AD by restoring the skin barrier?…”
Section: Therapeutic Management Of Admentioning
confidence: 99%